The Implementation of Information Systems in Facilities and Infrastructure Management at Muhammadiyah Vocational School 2 Salam - Giandatenaya, Gibranamar (Jurnal Ilmiah Mandala Education (JIME), 2024)
Information systems in the current era is use important role in everything. In general, information systems play an important role as a single source of information that is easily accessible and as a material for making decisions regarding educational implementation programs. One aspect that requires the implementation of information systems is facilities and infrastructure. In general, facilities and infrastructure cover everything that is important within the material scope of the school. The aim of this research is to reveal an overview of the efforts of SMK Muhammadiyah 2 Salam in implementing information systems and their functions in managing school facilities and infrastructure. The research method used in this research is qualitative with a case study approach. The data collection technique was carried out by means of in-depth interviews. Data validation uses the member check technique while data analysis uses thematic techniques which include: 1). Reduction; 2). Presentation; 3). Conclusion. The results of the research explain that the implementation of information systems in facilities and infrastructure management efforts at Muhammadiyah 2 Salam Vocational School is still experiencing various obstacles. Some of these obstacles are the budget and organizational communication which is not yet effective.